Prevalence of E. histolytica and E. dispar by means of microscopy and ELISA in a Suburb of Lima - Cornejo Medina, William (1999)
OBJECTIVES: To assess the prevalence of E. histolytica and E. dispar in a marginal population of Callao, Lima, using ELISAs. MATERIAL AND METHODS: Two ELISAs were used, one of them for both Entamoeba species (Entamoeba-ELISA), and an E. histolytica-specific ELISA. RESULTS: 128 stool samples from randomized Callao inhabitants were microscopically examined. Thirteen (10%) were microscopically diagnosed as having E. histolytica or E. dispar infection; and 7 (6%) were positive to Entamoeba–ELISA (sensitivity = 54%). Five of the 115 samples without cysts of E. histolytica or E. dispar were Entamoeba ELISA positive (specificity = 96%). All samples were negative to the E. histolytica-specific ELISA. CONCLUSIONS: The correlation between the microscopical identification and Entamoeba-ELISA was not good, it may be due to an overvaluation of the morphological diagnosis.